Diagoras of Melo and Theodore of Cyrene: two atheists? - Casertano, Giovanni (Revista Archai, 2023)
Diagoras and Theodorus are two of the atheists remembered in several catalogues of atheists in Antiquity, the first of which dates back to the 2nd century BC, and from then on invariably referredto by the ancients and to the present day as atheists. In fact, the atheism condemned in Athens had its roots in the pre-Socratic philosophical and scientific culture, whose fundamentally "materialistic" imprint is authoritatively testified to by Aristotle (MetaphysicsI 983b5-10). The philosophies of Anaximander, Anaximenes, Xenophanes, Heraclitus, Anaxagoras, Diogenes of Apollonia, and of course the Atomists and Sophists offered, albeit in different ways, not only some important support for the critique of traditional divinities, but also for the philosophical foundations of atheism. Diagoras has nothing to do with this tradition; even some events in his life may at most merit the accusation of being impious, but not of being an atheist. heodore appears to be of a different cultural temperament, close not only to the culture of the Cyrenaic school, but also to that of the Cynics and the Sophists. We have not only references to his philosophical doctrines, but also clear evidence of his atheism, having dedicated himself to "radically eliminating common beliefs in the gods". In conclusion, while Diagora's name can safely be removed from the catalogues of atheists, Theodore's is rightly included.